Trends in estrogen and progesterone receptors in prostate cancer: a bibliometric analysis - Liao, Wenqiang; Sui, Xuxia; Hou, Gaoming; Yang, Mei; Lin, Yuxue; Lu, Junjie; Yang, Qingtao (Frontiers in Oncology, 2023)
Introduction The bibliometric analysis aims to identify research trends in estrogen receptor (ERs) and progesterone receptor (PRs) in prostate cancer (PCa), and also discuss the hotspots and directions of this field. Methods 835 publications were sourced from the Web of Science database (WOS) from 2003 to 2022. Citespace, VOSviewer, and Bibliometrix were used for the bibliometric analysis. Results The number of published publications increased in early years, but declined in the last 5 years. The United States was the leading country in citations, publications, and top institutions. Prostate and Karolinska Institutet were the most publications of journal and institution, respectively. Jan-Ake Gustafsson was the most influential author based on the number of citations/publications. The most cited paper was “Estrogen receptors and human disease” by Deroo BJ, published in the Journal of Clinical Investigation. The most frequently used keywords were PCa (n = 499), gene-expression (n = 291), androgen receptor (AR) (n = 263), and ER (n = 341), while ERb (n = 219) and ERa (n = 215) further emphasized the importance of ER. Conclusions This study provides useful guidance that ERa antagonists, ERb agonists, and the combination of estrogen with androgen deprivation therapy (ADT) will potentially serve as a new treatment strategy for PCa. Another interesting topic is relationships between PCa and the function and mechanism of action of PRs subtypes. The outcome will assist scholars in gaining a comprehensive understanding of the current status and trends in the field, and provide inspiration for future research.